Peran Desain Kemasan dan Penyajian Dalam Keputusan Pembelian Es Krim Lidah Buaya - Siti Zaleha; R R Siti Astuti; Nur Rohmah Lutfi A'yuni (PAKIS JOURNAL INSTITUTE, 2026)
This study aimed to examine the effect of packaging design as well as product presentation on consumer purchasing decisions for aloe vera ice cream. The study employed a quantitative method with an associative approach. Data were obtained through questionnaires distributed to 31 respondents who had previously purchased the product, selected using purposive sampling techniques. The research instruments were tested for validity and reliability, and the data were analyzed using multiple linear regression with the assistance of SPSS software. Prior to hypothesis testing, classical assumption tests were conducted to ensure the suitability of the regression model. The results showed that packaging design and product presentation simultaneously had a significant effect on purchasing decisions. However, partially, packaging design did not have a significant effect on purchasing decisions. In contrast, product presentation had a positive and significant effect and became the most dominant factor influencing consumer purchasing decisions. The coefficient of determination indicated that the model had a moderate explanatory ability, suggesting that other factors outside this study also influenced consumer purchasing decisions. In conclusion, purchasing decisions were more influenced by the visual appearance of product presentation than by packaging design itself. M Therefore, product development should focus more on improving presentation quality while continuing to optimize packaging design as a supporting factor for product attractiveness.